Fundamentals of machining and machine tools - Boothroyd, Geoffrey; Knight, Winston A (London: CRC Taylor & Francis, 2017)
About the Book: Fundamentals of Metal Machining and Machine Tools: 3rd Edition In the more than 15 years since the second edition of Fundamentals of Machining and Machine Tools was published, the industry has seen many changes. Students must keep up with developments in analytical modeling of machining processes, modern cutting tool materials, and how these changes affect the economics of machining. With coverage reflecting state-of-the-art industry practice, Fundamentals of Machining and Machine Tools, Third Edition emphasizes underlying concepts, analytical methods, and economic considerations, requiring only basic mathematics and physics. This book thoroughly illustrates the causes of various phenomena and their effects on machining practice.
Keywords: Mechanical Engineering